Implementasi Kurikulum Merdeka dan Student Wellbeing : Mediasi Kepercayaan Diri Siswa - Fitriatin, Eny (FKIP Universitas Islam Jember, 2024)
This study evaluates the impact of implementing the Merdeka Curriculum on the well-being of elementary school students in Jember Regency participating in the Program Sekolah Penggerak (PSP), with self-confidence as a mediator. A quantitative survey method was employed, involving students from grades 4 to 6, with data analyzed using structural equation modeling (SEM). The findings indicate that the implementation of the Merdeka Curriculum significantly enhances student well-being (β = 0.45, p < 0.001), and self-confidence acts as a significant mediator in this relationship (β = 0.35, p < 0.01). These results highlight the importance of psychological factors, such as self-confidence, in optimizing the effectiveness of educational policy implementation. Aligning with self-determination theory, the study shows that autonomy and support in learning environments contribute to intrinsic motivation and student well-being. This study underscores the necessity for teacher training programs that integrate strategies to foster student self-confidence, ensuring more impactful outcomes of the Merdeka Curriculum. Future research should adopt qualitative methods and broader geographical scopes to validate these findings